Model regresi antara jumlah massa telur dengan kepadatan populasi larva Chironomidae (Diptera) : Percobaan laboratorium - Bambang Sulistiyarto (Fakultas Peternakan Universitas Kristen Palangka Raya, 2017)
This study aims to determine the relationship between the number of egg masses laid by their brood and the population density of Chironomidae larvae in waters. The laboratory experiment was carried out by spreading Chironomidae egg masses with 4 density levels and 3 replications: (A) 3 egg masses / container (B) 6 egg masses / container (C) 9 egg masses / container and (D) 12 egg masses /container. Chironomidae larvae population counted after 8 days of maintenance. Based on this study, population densities of Chironomidae larvae ranged from 2576 to 5817 individuals / m2 with body lengths ranging from 9.067 to 14.265 mm. Increasing the number of egg masses were laid, will decrease the density of larval Chironomidae follow cubic regression model Y = 18287 - 443.6 X + 4.015 X2 - 0.01143 X3